Effects of thermal treatment of ZnO-ZnCr2O4 catalyst on the particle size and product selectivity in dehydrocyclization of crude glycerol and ethylenediamine - Sarkari, Reema; Krishna, Vankudoth; Sudhakar, Medak; Rao, Tumula Venkateshwar; Padmasri, Aytam Hari; Srinivas, Darbha; Venugopal, Akula (Kinetics and Catalysis, 2016)
The ZnO-ZnCr2O4 (Zn-Cr-O) sample obtained by decomposition of Zn-Cr hydrotalcite precursor was subjected to the thermal treatment at different temperatures and the physico-chemical properties of the Zn-Cr-O system were compared with its catalytic behavior in dehydrocyclization of crude glycerol and ethylenediamine (EDA). Upon high temperature treatment of Zn-Cr-O the Cr6+ ions underwent autoreduction to form stable Cr3+ species and the particle size of both ZnO and ZnCr2O4 increased dramatically. Thermal effect did not influence the intermolecular cyclisation of EDA to form pyrazine. By contrast, an inversely proportional dependence was found between the rate of formation of 2-methylpyrazine and the particle size of Zn-Cr-O whereas the rate of 2-pyrazinylmethanol was directly proportional to the particle size.

Highly dispersed MnOx nanoparticles on shape-controlled SiO2 spheres for ecofriendly selective allylic oxidation of cyclohexene - Rao, Bolla Govinda; Sudarsanam, Putla; Rao, Tumula Venkateshwar; Amin, Mohamad Hassan; Bhargava, Suresh K.; Reddy, Benjaram M. (Catalysis Letters, 2020)
Shape-controlled metal nanomaterials are considered as a unique class of catalysts because of their synergistic size- and shape-dependent catalytic properties. This work reports the synthesis of a novel size- and shape-controlled catalyst, consisting of highly dispersed MnOx nanoparticles (average particle size of 4.5 nm) on shape-controlled SiO2 nanospheres (250-300 nm) for selective cyclohexene oxidation using air as the oxidant under solvent- and base-free conditions. The MnOx/SiO2 catalyst exhibited an excellent cyclohexene conversion (92%) with a high selectivity (96%) to the allylic products (2-cyclohexene-ol and 2-cyclohexene-one) under mild conditions, outperforming various SiO2 supported CoOx, FeOx, and CuOx catalysts. The better performance of shape-controlled MnOx/SiO2 nanocatalyst is due to high redox nature of Mn, uniform dispersion of smaller sized MnOx nanoparticles, and synergetic interaction between MnOx and SiO2 spheres, as evidenced by XPS and TEM studies. Further, the MnOx/SiO2 catalyst could be reused at least 5 times for selective cyclohexene oxidation with a negligible loss in its catalytic performance, indicating the excellent stability of shape-controlled metal nanocatalysts in organic synthesis under economically viable and mild conditions.
Keywords: Cyclohexene oxidation; MnOx nanoparticles; Shape-controlled catalyst; SiO2 nanospheres; Structure-performance relationship; Synergetic interaction